Comparision of Induction Characteristics and Hemodynamic Parameters of Propofol Versus Etomidate in Patients Undergoing Surgeries under General Anaesthesia, a Bispectral Index Guided Study - Shivanna, Dr. Poornima (International Journal of Innovative Research in Medical Science, 2017)
Background and Objective: - The aim of the study is to compare hemodynamic parameters and side effects of both drugs in order to choose a better induction agent. Materials and Methods: - This is a randomised double-blind study conducted at Bangalore Medical College and Research Institute on 70 patients scheduled for elective surgeries under general anaesthesia from october 2013 to may 2015. 70 patients were randomly allocated into either group P (propofol group) and to group E (etomidate group) of 35 each. All patients premedicated with inj.midazolam 0.02mg/kg IV, inj. Fentanyl 2 microgm/kg IV. Group P received propofol infusion at 0.5 mg/kg/hr and group E at 0.05mg/kg/hr until Bispectral index value dropped to 50. Then patients were intubated with vecuronium 0.1mg/kg and anaesthesia maintained according to institutional protocol followed by extubation after adequate recovery. Hemodynamic parameters and side effects during induction were recorded between both groups until the infusion of study drug. Results: - There was statistically significant fall in heart rate in propofol group ( Group P) from the baseline starting from 3 minutes of induction upto 10 minutes with p value < 0.05 and systolic, diastolic and mean arterial pressure with p value <0.01.There was no significant change in heart rate and blood pressure in etomidate ( Group E) starting from baseline. 32 patients (91.5%) in propofol group had pain compared to 9 patients (28.5%) in etomidate group with p value <0.001. Myoclonus was observed among 4 patients induced with propofol when compared to 27 patients induced with etomidate with p value <0.001. Incidence of nausea was 22.9% in propofol group compared to 71.4% in etomidate group and incidence of vomiting was 22.8% in propofol group compared to 77.1% in etomidate group both with p value <0.001. Conclusion: In conclusion, etomidate is better for its hemodynamic stability over propofol along with less incidence of pain on injection. Only drawback was incidence of myoclonus and post-operative nausea and vomiting.